C-Reactive Protein, Advanced Glycation End Products, and Their Receptor in Type 2 Diabetic, Elderly Patients with Mild Cognitive Impairment - Gorska-Ciebiada, Malgorzata; Saryusz-Wolska, Malgorzata; Borkowska, Anna; Ciebiada, Maciej; Loba, Jerzy (Frontiers in Aging Neuroscience, 2015)
Objective: The aim of the study was to evaluate serum levels of AGEs (advanced glycation end products), RAGE (receptor for advanced glycation end products) and CRP (C-reactive protein) in elderly patients with T2DM with and without mild cognitive impairment (MCI) and to determine the predictors (including AGEs, RAGE and CRP levels) of having MCI in elderly patients with type 2 diabetes. Methods: 276 diabetics elders were screened for MCI (using the Montreal Cognitive Assessment: MoCA score). Data of biochemical parameters and biomarkers were collected. Results: Serum AGEs, RAGE and CRP levels were significantly increased in MCI patients compared to controls. In group of patients with MCI serum RAGE level was positively correlated with AGEs level and with CRP level. RAGE, AGEs and CRP concentrations were positively correlated with HbA1c levels and negatively correlated with MoCA score. The univariate logistic regression models revealed that variables which increased the likelihood of diagnosis of MCI in elderly patients with type 2 diabetes were: higher levels of HbA1c, RAGE, AGEs, CRP, TG, lower level of HDL cholesterol, previous CVD, HA or use of HA drugs, hiperlipidaemia, retinopathy, nephropathy, increased number of co-morbidities, older age and less years of formal education. HA or use of HA drugs, previous CVD, higher level of RAGE and CRP, older age and less years of formal education are the factors increasing the likelihood of having MCI in elderly patients with type 2 diabetes in multivariable model. Conclusions: In summary, serum AGEs, RAGE and CRP are increased in the circulation of MCI elderly diabetic patients compared to controls. A larger population-based prospective study needs to be performed to further confirm the relationship between AGEs, RAGE and the cognitive decline or progress to dementia.